Enhancing consistency in arbuscular mycorrhizal trait-based research to improve predictions of function - Pedro M. Antunes; Sidney L. Stürmer; James D. Bever; Pierre-Luc Chagnon; V. Bala Chaudhary; Coline Deveautour; Catherine Fahey; Vasilis Kokkoris; Ylva Lekberg; Jeff R. Powell; Carlos A. Aguilar-Trigueros; Haiyang Zhang (Mycorrhiza, 2025)

Arbuscular mycorrhizal fungal spore communities and co-occurrence networks demonstrate host-specific variation throughout the growing season - Jacob R. Hopkins; James D. Bever (Mycorrhiza, 2024)
Microbial community assembly involves a series of ecological filtering mechanisms that determine the composition of microbial communities. While the importance of both broad and local level factors on microbial communities has been reasonably well studied, this work often is limited to single observations and neglects to consider how communities change over time (i.e., seasonal variation). Because seasonal variation is an important determinant of community assembly and determines the relative importance of community assembly filters, this represents a key knowledge gap. Due to their close associations with seasonal variation in plant growth and fitness, arbuscular mycorrhizal (AM) fungi are useful groups for assessing the importance of seasonal dynamics in microbial community assembly. We tested how seasonal variation (spring vs. summer), plant life history stage (vegetative vs. flowering), and host plant species ( Baptisia bracteata var. leucophaea & Andropogon gerardii ) influenced AM fungal spore community assembly. AM fungal spore community temporal dynamics were closely linked to plant host species and life history stage. While AM fungal spore communities demonstrated strong turnover between the spring (e.g., higher sporulation) and late summer (e.g., higher diversity), the strength and direction of these changes was modified by host plant species. Here we demonstrate the importance of considering temporal variation in microbial community assembly, and also show how plant-microbe interactions can modify seasonal trends in microbial community dynamics.

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Sensitivity to AMF species is greater in late‐successional than early‐successional native or nonnative grassland plants - Tanya E. Cheeke; Chaoyuan Zheng; Liz Koziol; Carli R. Gurholt; James D. Bever (Ecology, 2019)
Sensitivity of plant species to individual arbuscular mycorrhizal ( AM ) fungal species is of primary importance to understanding the role of AM fungal diversity and composition in plant ecology. Currently, we do not have a predictive framework for understanding which plant species are sensitive to different AM fungal species. In two greenhouse studies, we tested for differences in plant sensitivity to different AM fungal species and mycorrhizal responsiveness across 17 grassland plant species of North America that varied in successional stage, native status, and plant family by growing plants with different AM fungal treatments including eight single AM fungal isolates, diverse mixtures of AM fungi, and non‐inoculated controls. We found that late successional grassland plant species were highly responsive to AM fungi and exhibited stronger sensitivity in their response to individual AM fungal taxa compared to nonnative or early successional native grassland plant species. We confirmed these results using a meta‐analysis that included 13 experiments, 37 plant species, and 40 fungal isolates (from nine publications and two greenhouse experiments presented herein). Mycorrhizal responsiveness and sensitivity of response (i.e., variation in plant biomass response to different AM fungal taxa) did not differ by the source of fungal inocula (i.e., local or not local) or plant family. Sensitivity of plant response to AM fungal species was consistently correlated with the average mycorrhizal response of that plant species. This study identifies that AM fungal identity is more important to the growth of late successional plant species than early successional or nonnative plant species, thereby predicting that AM fungal composition will be more important to plant community dynamics in late successional communities than in early successional or invaded plant communities.

Whole body magnetic resonance imaging (WB-MRI) and brain MRI baseline surveillance in TP53 germline mutation carriers: experience from the Li-Fraumeni Syndrome Education and Early Detection (LEAD) clinic - Jasmina Bojadzieva; Behrang Amini; Suzanne F. Day; Tiffiny L. Jackson; Parijatham S. Thomas; Brandy J. Willis; Whitney R. Throckmorton; Najat C. Daw; Therese B. Bevers; Louise C. Strong (Familial Cancer, 2018)

User Perceptions and Reactions to an Online Cancer Risk Assessment Tool: a Process Evaluation of Cancer Risk Check - Shelly R. Hovick; Therese B. Bevers; Jennifer Irvin Vidrine; Stephanie Kim; Phokeng M. Dailey; Lovell A. Jones; Susan K. Peterson (Journal of Cancer Education, 2017)

Brain responses to erotic and other emotional stimuli in breast cancer survivors with and without distress about low sexual desire: a preliminary fMRI study - Francesco Versace; Jeffrey M. Engelmann; Edward F. Jackson; Aurelija Slapin; Kristin M. Cortese; Therese B. Bevers; Leslie R. Schover (Brain Imaging and Behavior, 2013)

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Redox chemistry of tungsten and iron–sulfur prosthetic groups in Pyrococcus furiosus formaldehyde ferredoxin oxidoreductase - Emile Bol; Loes E. Bevers; Peter-Leon Hagedoorn; Wilfred R. Hagen (JBIC Journal of Biological Inorganic Chemistry, 2006)